An Analysis of The Study Scientific Approach Implementation to Develope The Active Learning of Science in The Early Childhood (Journal of Primary Education, 2019)
This research aimed to analyze the study implementation scientific approach to develop the active learning of science in early childhood. This research used a qualitative method to know the result of the research that can be described as factually and profound. For data collection was used interview, observation, and study the documentation by using an interactive data analysis. For the validity data, there is three kinds of triangulation was used a technique of triangulation, source of triangulation, and the theory of triangulation. The result of the research showed that to develop the science academy learning in early childhood should be implemented into five components scientific approach such as observing, questioning, experimenting, associating, and networking. Through five scientific approach components the active learning of science that was seen in children were children bound actively during learning process, children bound in solving problem during experimenting, children were brave in questioning to the teacher, children were associating to the others friends related to the result of their experiment, children train themselves to solve their problem in their experimenting; then, they conclude the result based on their experiment. Based on the scientific approach, the active learning of science in early childhood developed well. Through the research, hopefully, it gave benefit to the society, such as enhancing their knowledge, especially in early childhood education. Also, the society was able to develop the potential of academic research, especially the active learning of science in early childhood.